Transformational Learning Design: Developing an Environment-Based Mathematics Model for Quality and Outcome Improvement - Kurniawan Kurniawan; Arismunandar Arismunandar; Abdul Haling (Journal of Strategy and Transformation in Educational Management, 2025)
This study develops and evaluates the Environment-Based Mathematics Learning (EBML) model as a transformational instructional approach to improve learning quality and outcomes in secondary mathematics. The model integrates environmental exploration, contextual problem-solving, and collaborative inquiry to strengthen students’ conceptual understanding. Using a developmental research design, EBML was validated through expert assessments, classroom observations, student responses, and pre–post learning performance. The validation results show a high level of conceptual and structural validity (average score 3.72), while practicality tests indicate strong acceptance among teachers (90.63%) and students (92.16%). Effectiveness analysis demonstrates significant improvement in learning outcomes, with achievement increasing from 62.06% to 87.79% and a gain index of 0.68. Student activity also remained consistently high across all learning stages. The findings confirm that EBML is a feasible, effective, and contextually rich model that transforms mathematics learning by connecting abstract concepts to meaningful environmental experiences.